2015
DOI: 10.17770/sie2015vol2.458
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Project –Based Learning in the Acquisition of English as a Foreign Language

Abstract: <p><em>In the last years the project – based learning has become a popular teaching method in Latvia. Project work is a student-centred teaching approach; it motivates students to use language in real life situations and involves a great number of students’ feelings, talents, skills and knowledge in the education process. It is a way to express students’ own decisions, experience, almost dreams. This approach can be used for both: small kids (beginners’ level) and for adolescents (upper-intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 3 publications
3
17
0
1
Order By: Relevance
“…What are trainee teachers" Masters students" motivational attitudes towards L2 English learning through PBL, as measured by a perception questionnaire? Based on RQ 1, we predict that positive attitudes will be shown towards L2 English learning through PBL, in line with previous empirical research in the field (Supe and Aivars, 2015). These answers will be triggered by the properties that characterize this teaching methodology, namely, it allows development of (a) autonomy as they are responsible for their own learning; (b) real language use; (c) capacity to monitor the learning process and the final project design; (d) skills to read, gather and select information; and (d) abilities to find solutions for problem-solving tasks (Pham, 2018;Poonpon, 2011;Simpson, 2011;Tan, 2004a;2004b).…”
Section: Research Questionssupporting
confidence: 84%
See 3 more Smart Citations
“…What are trainee teachers" Masters students" motivational attitudes towards L2 English learning through PBL, as measured by a perception questionnaire? Based on RQ 1, we predict that positive attitudes will be shown towards L2 English learning through PBL, in line with previous empirical research in the field (Supe and Aivars, 2015). These answers will be triggered by the properties that characterize this teaching methodology, namely, it allows development of (a) autonomy as they are responsible for their own learning; (b) real language use; (c) capacity to monitor the learning process and the final project design; (d) skills to read, gather and select information; and (d) abilities to find solutions for problem-solving tasks (Pham, 2018;Poonpon, 2011;Simpson, 2011;Tan, 2004a;2004b).…”
Section: Research Questionssupporting
confidence: 84%
“…Although 52% of students considered that projects were an effective learning method before they experienced PBL, 82% reported that their positive attitude towards studying through projects increased after the experiment. Supe and Aivars (2015), also reported that 53% of the L2 English learners preferred projects to ordinary English lessons (20%) before the experiment. These frequency rates increased after the experiment for both project work (86%) and the attitudes for ordinary lesson decreased (6%) after the experiment.…”
Section: Empirical L2 English Learning Work On Project-based Learningmentioning
confidence: 91%
See 2 more Smart Citations
“…While this teaching and learning approach is sensible, logical and easily applicable in courses related to development of professional skills, such as information technology, human resource management, sales or marketing, where students are able to create authentic products or solutions to real problems, PBL is also a highly effective teaching method in foreign language courses, especially courses of language for professional purposes. Projects are also used in primary and secondary school instruction with various sets of goals and purposes (Supe & Kaupuzs, 2015). As the main focus of language instruction is still the development of the four language skills, we can connect all of them to PBL (Mikulec & Miller, 2011).…”
Section: Resultsmentioning
confidence: 99%